Immunogenicity Evaluation Of A133 And Ss-Ir: Development Of Vaccine Candidates Against Strongyloides Stercoralis - Wong, Matthew Tze Jian (2024)
Strongyloidiasis, caused by the nematode Strongyloides stercoralis, remains a threat to global public health. To date, a vaccine against strongyloidiasis remains unavailable and there was no significant development in this area after discovering the potential of recombinant protein Ss-IR as a vaccine candidate in 2011. In light of recent developments in the diagnosis of strongyloidiasis, A133 emerged in 2021 as an excellent diagnostic antigen, prompting curiosity for its potential as a vaccine candidate. Therefore, this study aimed to evaluate the efficacy of recombinant protein A133 in comparison to Ss-IR, as a potential vaccine candidate against S. stercoralis by investigating humoral and cellular immune responses in immunised mice.